Tetracycline and chloramphenicol exposure induce decreased susceptibility to tigecycline and genetic alterations in AcrAB-TolC efflux pump regulators in Escherichia coli and Klebsiella pneumoniae. - Nian Anwar Nasralddin; Mehri Haeili; Sasan Karimzadeh; Fatemeh Alsahlani (PLoS ONE)
Tigecycline (Tgc), a third-generation tetracycline is found as the last line of defense against multi-drug resistant bacteria. Recent increased rate of resistance to tgc, a human-restricted agent among animal bacteria poses a significant global health challenge. Overuse of first generation tetracyclines (Tet) and phenicols in animals have been suggested to be associated with Tgc resistance development. In the current study we aimed to determine the effect of tetracycline (Tet) and chloramphenicol (Chl) overexposure on Tgc susceptibility. A Tet and Chl-susceptible isolate of K. pneumoniae and E. coli were exposed to successively increasing concentrations of tetracycline and chloramphenicol separately until a ≥4 times increase in Tet and Chl MICs was observed. Susceptibility changes to several antimicrobial agents were tested using disk diffusion and broth dilution methods. The genetic alterations of genes coding for major AcrAB regulators including acrR (repressor of acrAB), ramR (repressor of ramA), soxR (repressor of soxS) in K. pneumoniae and lon (proteolytic degradation of MarA), marR (repressor of marA), acrR and soxR in E. coli were investigated. The expression level of acrB was measured using reverse transcription-quantitative polymerase chain reaction (RT-qPCR) method. The excessive exposure (15 to 40 selection cycles) of studied bacteria to both antibiotics significantly decreased susceptibility of Tet-resistant (R) and Chl-R variants of E. coli (n = 6) and K. pneumoniae (n = 6) to several groups of antibiotics including tigecycline (4-16 and 8-64 times respectively) and quinolones. About 58% of variants (n = 7) carried genetic alterations in AcrAB regulators including ramR (frameshift mutations/locus deletion), MarR (L33R, A70T, G15S amino acid substitutions) and Lon (L630F change, frameshift mutation) which were associated with acrB upregulation. Our study demonstrated the capacity of chloramphenicol and tetracycline exposure for selection of mutants which revealed tigecycline resistance/decreased susceptibility mostly mediated by active efflux mechanism. Unaltered acrB expression level in some strains indicates possible contribution of other efflux pumps or non-efflux-based mechanisms in the development of multiple- antibiotic resistance phenotype.